Mediasi Online sebagai Alternatif Penyelesaian Sengketa Hubungan Industrial pada Masa Pandemi Covid-19 di Indonesia - Dewa Putu Ade Wicaksana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
The massive spread of the Covid-19 pandemic has hampered the process of resolving conventional industrial relations disputes in Indonesia. Online mediation as an alternative dispute resolution forum that is capable of accommodating the interests of the parties according to the formal rules of industrial relations dispute settlement in collaboration with technology. The problems of this study are: 1. How is the arrangement of online mediation as an alternative to resolving industrial relations disputes during the COVID-19 pandemic in Indonesia; 2. How is the validity of the results of online mediation as an alternative to resolving industrial relations disputes during the COVID-19 pandemic. The research method used is a normative legal research method that examines legal norms substantially, based on a conceptual approach and a legal approach. The collection of legal materials using document study techniques. The results of this study indicate that the Law. No. 30 of 1999 and Law. No. 2 of 2004 has implicitly provided space for online mediation as an alternative instrument for resolving industrial relations disputes. Indonesia does not yet have a legal umbrella both formal and material that regulates "lex specialis" regarding online mediation as well as written agreements resulting from online mediation as an alternative to resolving industrial relations disputes during the COVID-19 pandemic, does not yet have legally binding power, so it is still vulnerable to be violated by the parties.